Time of migration
The spring migration of the alewife is shown from the sea, where it matured, to its freshwater spawning grounds. When the eggs hatch, the small fish eat plankton, and when they are about one inch (2.5 centimetres) long they swim to the sea where they will mature and return to spawn in three or four years.